Macroeconomic Policy Frameworks for Resource-Rich Developing Countries. (Policy Papers; Policy Paper ;, 2012)
This paper aims to widen the prism through which Fund policy analysis is conducted for resource-rich developing countries (RRDCs). While all resource-rich economies face resource revenue exhaustibility and volatility, RRDCs face additional challenges, including lack of access to international capital markets and domestic capital scarcity. Resource exhaustibility gives rise to inter-temporal decisions of how much of the resource wealth to consume and how much to save, and revenue volatility calls for appropriate fiscal rules and precautionary savings. Under certain conditions, it would be optimal for a significant share of a RRDC's savings to be in domestic real assets (e.g., investment in domestic infrastructure), though absorptive capacity constraints need to be tackled to promote efficient spending and short-run policies are needed to preserve macroeconomic stability. The objective of this paper is to develop new macro-fiscal frameworks and policy analysis tools for RRDCs that could enhance Fund policy advice.